Pengembangan Media Pembelajaran Berbasis Construct 2 Untuk Meningkatkan Hasil Belajar Materi Organ Pencernaan Manusia pada Siswa Kelas V SDN Ngasem 1 - Purwaningtyas, Nuranisya; Susi Damayanti; Erwin Putera Permana (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This research is motivated by the results of preliminary studies and the experience of researchers, who have found that in the learning process that takes place in the classroom there are problems related to the use of learning media. In learning, teachers only use teaching methods and tend to use textbooks as a teaching tool. The impact of these problems is that most students do not understand the content of their learning material, especially when it comes to the human digestive system. So the researchers developed Construct 2 learning media for the material of the human digestive organs. So that teachers and students can learn and access the material at any time. This study aims to determine the validity, usefulness and effectiveness of the Construct 2 learning media used. Researchers used qualitative and quantitative research methods and the development model used in this study, namely ADDIE (Analysis, Design, Development, Implementation, Evaluation). The data in this study were obtained through the validation of material experts and media experts. The conclusions from the results of this study on construct 2-based learning media are (1) getting an average score of 87% from material experts and media experts (2) being explained practically and getting an average score of 89.11% (3) being declared effective besed on the average student score as many as 90.3% of students meet the minimum completeness criteria. As a result, it is possible to conclude that Construct 2 learning process and can improve student learning outcomes in subject matter .